Differences Between Supplier and Customer Experiences of Marketing Mix in the Construction Industry - Al-Fadly, Ahmad (Frontiers in Built Environment, 2022)
Suppliers often contend they “know” best when it comes to what the customer wants. Yet, despite using advanced models, such as the 7P (product, place, price, promotion, people, process, and physical evidence) marketing mix, companies can fail to meet their service objectives because customers perceive services from their own perspective. This difference in perspective presents a knowledge gap that requires it to be filled in an objective way. This research study elucidates how differences between supplier perception and customer perception of delivery are objectively identified. In this study, the target population consisted of the managers of the construction companies in Kuwait and their customers as individual property owners of residential, commercial, and industrial buildings. Discrete questionnaires consisting of the 7P marketing mix constructs were created specifically for the supplier and customer. Using a five-point Likert scale, data from 210 supplier staff and 210 customers were collected from the construction industry. The structural equation modeling (SEM) established the beta coefficients of latent variables reflecting the perceptions of both the supplier and customer. Both models were tested for internal consistency reliability using Cronbach’s alpha, and convergent validity was established based on the standardized factor loading and average variance extracted (AVE). In addition, discriminant validity was established using AVE and correlations. The differences between the standardized coefficients of supplier and customer coefficients were then tested against their pooled variance. The results show that suppliers tend to have a higher perception of their delivery on some constructs, while customers maintained a higher perspective on other constructs, that is, suppliers perceived that their product, place, price, and process were adequate, while customer data indicated otherwise. However, it was promising that the constructs of promotion, physical evidence, and people were more favorable among customer perceptions than supplier expectations. Interestingly, customers perceived that the people factor behind the construction industry was excellent. The findings recommend that suppliers scale their perceptions to be closer to the reality perceived by the customers. The study concludes that this approach of evaluating supplier–customer perceptions is highly beneficial to the supplier.